Synthesis and photophysical properties of fluorescent 2,1,3-benzothiadiazole-triazole-linked glycoconjugates: selective chemosensors for Ni(II) - Moro, Angélica V.; Ferreira, Patrícia C.; Migowski, Pedro; Rodembusch, Fabiano S.; Dupont, Jairton; Lüdtke, Diogo S. (Tetrahedron, 2013)
The synthesis of new fluorescent 2,1,3-benzothiadiazole-triazole-linked glycoconjugates is described by a straightforward synthetic route, using a copper(I)-catalyzed azide–alkyne 1,3-dipolar cycloaddition (CuAAC). UV–visible (UV–vis) and steady-state fluorescence in solution were applied in order to characterize its photophysical behavior. The dyes present absorption in the violet region with fluorescence emission in the cyan-green region, which can be related to the methoxy derivatives due to an intramolecular charge transfer (ICT) in the excited state. The studied derivatives present potential optical application since combine large extinction coefficient for absorption, large Stokes shift and high fluorescence emission. Additionally, these dyes exhibit binding selectivity to Ni+2 among a series of cations in CH3CN solution. [Display omitted]